Knowledge, Attitude, and Contraceptive Preferences Among Postpartum Women in Izzi, Ezza South, and Ikwo Local Government Areas of Ebonyi State, Nigeria - Rita Anaba; Emmanuel Ugwa; Iwasam Agbor; Matthew Nwali; Bright Orji (Baqiyatallah University of Medical Sciences, 2018)
Background: The fertility rate is high and the contraceptive prevalence rate is very low in Nigeria. Thus, women in Nigeria are exposed to the dangers of unwanted and unplanned pregnancies. Objective: The current study aimed to determine the levels of knowledge, attitudes, and contraceptive preferences among couples in selected health facilities in Ebonyi State so as to recommend a package of intervention to increase contraception uptake. Methods: This cross-sectional descriptive quantitative study used questionnaires administered by the researchers themselves among 128 postpartum women who were current users of contraceptive methods in Izzi, Ezza South, and Ikwo local government areas of Ebonyi State, Nigeria from January 1, 2016 to June 30, 2017. Informed consent was obtained from participants. Data was analyzed using SPSS version 20. Simple percentages were used to report categorical variables. Results: The study results showed that most of the respondents (49%) had a secondary education, were aged above 20 years, and were mainly employed as civil servants with an average monthly income of $47.20. About 69% had less than 5 living children. Most respondents knew about contraception as a means of delaying pregnancy or limiting the number of children (37%) and recommended its use for family/society (46%). The most commonly used contraceptive methods were implants and injectable ones, while the IUD was the least preferred. Both implants and injectable contraceptives were recommended by friends and believed to be highly effective. Conclusion: The current study showed that knowledge and positive attitude of participants towards family planning was high, comparable to studies in other parts of the world. Further research on determinants of postpartum use of family planning methods among this population is recommended.